2019
DOI: 10.1097/rli.0000000000000515
|View full text |Cite
|
Sign up to set email alerts
|

Native T1 Mapping as an In Vivo Biomarker for the Identification of Higher-Grade Renal Cell Carcinoma

Abstract: Objectives The aims of this study were to identify higher-grade clear cell renal cell carcinoma (cRCC) with native T1 mapping and to histologically correlate the results with the collagen volume fraction. Materials and Methods For this institutional review board–approved, single-center prospective study, 68 consecutive patients received abdominal magnetic resonance imaging scans at 1.5 T between January 2017 and July 2018, using a Modified Look-Locker I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 41 publications
0
39
1
Order By: Relevance
“…Techniques using at least two acquisitions with different flip angles are commonly used for this purpose 32 but other techniques have also been evaluated in order to further optimize the accuracy of T1 mapping 33 . Furthermore, pathological tissue alterations as a result of disease processes such as extracellular matrix expression and tissue fibrosis can be noninvasively visualized and quantified based on changes in T1 relaxation properties 13,14,34,35 . Few studies have already evaluated non-contrast-enhanced T1 mapping for the diagnosis of PCa using different technical approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques using at least two acquisitions with different flip angles are commonly used for this purpose 32 but other techniques have also been evaluated in order to further optimize the accuracy of T1 mapping 33 . Furthermore, pathological tissue alterations as a result of disease processes such as extracellular matrix expression and tissue fibrosis can be noninvasively visualized and quantified based on changes in T1 relaxation properties 13,14,34,35 . Few studies have already evaluated non-contrast-enhanced T1 mapping for the diagnosis of PCa using different technical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, any further use of MOLLI for prostate imaging has not been reported yet. T1 measured with MOLLI has proven to be a robust imaging biomarker in cardiac MRI 13,14 as well as selected malignancies such as renal cell cancer with an excellent interreader agreement 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have so far investigated native T1 mapping to characterize the degree of tumor differentiation in high-grade renal cell carcinoma and neuroblastoma [ 24 , 25 ]. Data on native T1 mapping in clinical or experimental HCC are poor, and studies on the characterization of ECM composition using the MOLLI sequence are missing.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent preclinical study, Zormpas-Petridis et al found T1 mapping to reliably distinguish regions with different levels of tumor cell differentiation in an experimental mouse model of neuroblastoma [ 24 ]. In patients, native T1 mapping was successfully used to identify higher-grade renal cell carcinoma histologically validated by the collagen volume fraction [ 25 ]. However, to the best of our knowledge, there is as yet no preclinical or clinical study that has systematically investigated native T1 mapping sequences to characterize liver tumors in terms of ECM composition.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, low tumor T1 values have been correlated to increased necrosis, low water content, and high levels of proteins [59]. Native T1 mapping could also represent an in vivo biomarker for the differentiation of tumor grade [60]. Significant changes in T1 were shown in several pre-clinical models in response to therapy [59,61].…”
Section: Tissular Composition and Imagingmentioning
confidence: 99%